Association of laryngopharyngeal reflux (LPR) and central obesity - Roy, Steuphen Roy A/L Peter Joseph (2021)
Laryngopharyngeal reflux (LPR) is a common disease encountered in otolaryngology. The presentation differs from gastroesophageal reflux disease (GERD) despite sharing similar pathophysiology. There are various postulated risk factors to LPR amongst which is central obesity. The aim of this study is to establish central obesity as a risk factor in developing LPR. Methods This is a comparative cross-sectional study in which 180 patients who were 18 years old and above regardless of obesity status without confounding factors in causing laryngeal mucosal change such as smoking, malignancy, post nasal drip, treatment with proton pump inhibitors and pregnancy were enrolled. These patients were not diagnosed with LPR prior. No pH studies or empirical treatment with proton pump inhibitors were given before. Reflux symptom index (RSI) and reflux finding score (RFS) were used to screen for LPR sign and symptoms. Results 87 central-obese patients based on waist-to-hip ratio (0.9 and 0.85 for male and female respectively) and 93 non central-obese patients were recruited in this study. There was a significant higher value of both RSI and RFS in central-obese patients with significant positive correlation between these variables. Patients with central obesity might have a 2.6-fold higher probability of being diagnosed with LPR. Conclusion This study derived a linear correlation between central obesity and LPR based on the relatively simple and non-invasive RSI and RFS tool.